Frequency Detection of Multidrug-Resistant Staphylococcus Aureus and Associated Genes Isolated from Hospital Surfaces in Khyber Pakhtunkhwa - Shams, Umia; Bibi, Salma; Ali, Yasir; Iqbal, Talat; Alam, Intikhab; Khan, Muhammad Mubassir (Indus Journal of Bioscience Research, 2024)
This study investigates on the prevalence of multidrug-resistant Staphylococcus aureus and its associated resistance genes on hospital surfaces at the Medicine ward of a hospital in Khyber Pakhtunkhwa, Pakistan. In total, 60 surface samples were collected and examined using culturing, biochemical testing, antibiotic susceptibility testing (AST), and molecular analysis via Polymerase Chain Reaction (PCR). Results indicated that 28 samples (46.7%) were positive for S. aureus. Among these isolates, 46% were mecA positive and 39% were ermC positive. Resistance rates for the drugs were as high as 95% for penicillin, 46% for methicillin, and 39% for erythromycin, whereas the isolates remained susceptible to vancomycin. The findings highlight hospital surfaces, especially high-touch areas such as bed rails and bedside tables, as reservoirs for multidrug-resistant pathogens, posing a significant risk for nosocomial infections. The genetic analysis showed a strong correlation between the presence of mecA and ermC genes and phenotypic resistance patterns, underscoring the role of molecular diagnostics in resistance monitoring. The importance of this study lies in underlining the need for infection control measures to be tightened down at the earliest with routine disinfection of surfaces, more efficient hand hygiene, and antibiotic stewardship programs to limit the rise of MRSA. It further requires public awareness among healthcare staff and visitors for better infection prevention practices. The current study highlights the importance of controlling antimicrobial resistance within healthcare settings for the greater good of patients and society as a whole.